Kesetaraan pasangan usia subur (pus) dalam pengambilan keputusan KB di Kabupaten Gresik=The Quality of Eligible Couples in Decision Making of Family Planning in Gresik Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Husband's participation in family planning in Indonesia is low. The 1999 national social and economic survey showed that 98.1% active family planning members in Indonesia were woman and mothers and 1.9% were men or husbands. However, in the process of decision making for using contraception, the role of men was so dominant. The Indonesian health and demographic survey during 1991-1997 showed that the proportion of women who used contraception as chosen by their husbands decreased. On the other hand, the proportion of women who did not use contraception because of their husbands' refusal increased. The aim of this study was to find out the sociodemographic characteristics equality of eligible couples (education, job, income), husband's knowledge of family planning, husband-wife communication about family planning, and their relationship with decision making pattern in family planning aspect, i.e. decision making in deciding the number of children they want in the family and decision making in the use of contraception method. This was a non-experimental study by the using cross-sectional approach with survey technique. The analysis was quantitatively, was held in the regency of Gresik, East Java with all eligible couples in Gresik as population. The samples were husbands who are still considered as eligible couples and had at least 1 child. The samples were taken by using multistage random sampling and Chi-Square for statistical analysis. r decision to use contraception metnoa ^p